Characterization of circulating transfer RNA-derived RNA fragments in cattle - Casas, Eduardo; Cai, Guohong; Neill, John D. (Frontiers in Genetics, 2015)
The objective was to characterize naturally occurring circulating transfer RNA-derived RNA Fragments (tRFs) in cattle. Serum from eight clinically normal adult dairy cows was collected, and small non-coding RNAs were extracted immediately after collection and sequenced by Illumina MiSeq. Sequences aligned to transfer RNA (tRNA) genes or their flanking sequences were characterized. Sequences aligned to the beginning of 5’ end of the mature tRNA were classified as tRF5; those aligned to the 3’ end of mature tRNA were classified as tRF3; and those aligned to the beginning of the 3’ end flanking sequences were classified as tRF1. There were 3,190,962 sequences that mapped to transfer RNA and small non-coding RNAs in the bovine genome. Of these, 2,323,520 were identified as tRF5s, 562 were tRF3s, and 81 were tRF1s. There were 866,799 sequences identified as other small non-coding RNAs (MicroRNA, rRNA, snoRNA, etc.) and were excluded from the study. The tRF5s ranged from 28 to 40 nucleotides; and 98.7% ranged from 30 to 34 nucleotides in length. The tRFs with the greatest number of sequences were derived from tRNA of histidine, glutamic acid, lysine, glycine, and valine. There was no association between number of codons for each amino acid and number of tRFs in the samples. The reason for tRF5s being the most abundant can only be explained if these sequences are associated with function within the animal.